Institutional Racism and Activism in Thomas’s The Hate U Give - Pattnaik, Minushree; Sarangi, Itishri (International Journal of Psychosocial Rehabilitation, 2020)
Bigotry in any form is a state of intense mental, intellectual, spiritual deprivation. The paper focuses on police racism, social injustice, isolation and prevention of Civil Rights to minorities’. The paper aims at exploring how the culture of white racism, approves systemic racism and on the effectiveness of activism ‘Just Us for Justice’ in reforming the culture of police racism. The paper is on Angie Thomas work The Hate U Give (2017), which is about poverty, racism and police brutality. The young person is murdered during a roadside check-up by the young white officer as he supposed the black teen precarious. County officer’s deadly shot, in questionable situation raises anger among communities. The paper explores how and why Just Us for Justice combined with engaged resident activism, creatively and effectively engaged in organizing efforts to oppose police racism.